2017
DOI: 10.1089/fpd.2017.2303
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinical Salmonellosis in Veal Calves on the Recovery ofSalmonellain Lymph Nodes at Harvest

Abstract: The objective of this study was to determine the prevalence, serotypes, antimicrobial resistance phenotypes, and pulsed-field gel electrophoresis (PFGE) patterns of Salmonella recovered in feces and mesenteric and prefemoral lymph nodes (LNs) from cohorts of calves with and without a confirmed outbreak of salmonellosis. In a prospective cohort study, 160 calves from four farms without a reported outbreak (nonoutbreak farms) were sampled at farm and harvest. In addition, harvest samples from 80 calves of two fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Another shared feature in food animals is that S. Newport isolates are more likely resistant to various cephalosporins. Current studies also confirmed that S. Newport samplings from cattle and ground beef exhibited 64.3% ( Munoz-Vargas et al, 2017 ) and 40% ( Iwamoto et al, 2017 ) resistance to extend-spectrum cephalosporins, respectively. The CEP, FEP, and CAZ, belonging to cephem class, and aztreonam (ATM) belonging to monobactam class, are the detected classifiers in animal sub-populations.…”
Section: Discussionsupporting
confidence: 69%
“…Another shared feature in food animals is that S. Newport isolates are more likely resistant to various cephalosporins. Current studies also confirmed that S. Newport samplings from cattle and ground beef exhibited 64.3% ( Munoz-Vargas et al, 2017 ) and 40% ( Iwamoto et al, 2017 ) resistance to extend-spectrum cephalosporins, respectively. The CEP, FEP, and CAZ, belonging to cephem class, and aztreonam (ATM) belonging to monobactam class, are the detected classifiers in animal sub-populations.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, most auction facilities cannot be effectively cleaned and disinfected, and thus, are a common point of direct or indirect transmission of infectious diseases. Multidrug resistant strains of Salmonella spp., a bacterium known for intestinal outbreaks in calf populations, including Dublin, Typhimurium, and Newport are common causes of disease outbreaks at veal and dairy-beef facilities (32). Surplus calves, which frequently have FTPI (11), are particularly at risk for infection.…”
Section: Livestock Auctionsmentioning
confidence: 99%
“…Importation of calves from multiple farms and commingling within livestock auctions also result in high infectious disease pressure. Severe outbreaks of clinical salmonellosis are relatively common, and result in high levels of mortality in calves (32). "All-in all-out" practices (raising calves in similarly aged groups) and other internal biosecurity measures are commonly utilized; however, the introduction of pathogens will be difficult to control as long as calves are routinely aggregated in livestock auctions prior to arrival at the calf-raiser.…”
Section: Calf Healthmentioning
confidence: 99%
“…However, disruptions in the microbial structure facilitate intestinal colonization of opportunistic enteric pathogens, including Salmonella [ 18 ]. To overcome the colonization resistance, Salmonella uses invasion strategies, the host inflammatory response and the lymphatic system machinery, for survival, proliferation [ 19 ] and systemic dissemination with a subsequent lymph node colonization [ 20 , 21 ]. In an inflamed intestine, Salmonella uses gene-regulated virulence mechanisms mainly guided by the type III secretion system [ 22 ] to compete with the gut commensals, and establish systemic and chronic infections [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%